Airgun injuries in New Zealand, 1979-92. Issue 2 (June 1996) - Langley, J. D.; Norton, R. N.; Alsop, J. C.; Marshall, S. W.
Abstract : OBJECTIVES: To describe the epidemiology of serious airgun injury in New Zealand. METHODS: Cases were selected from the New Zealand Health Information Service's hospital inpatient morbidity data files for the period 1979 to 1992 inclusive. RESULTS: There were 718 airgun related injuries resulting in 1.56 injuries/100, 000 population/year. Males and 10-14 year olds had higher than average rates of injury. The majority of the incidents were unintentional. There has been a marked decline in injury rates since 1989. CONCLUSIONS: Airgun injuries, while not as serious as powder firearm injuries, account for a significant personal and societal burden. The results suggest that strategies aimed at controlling these injuries, especially those pertaining to children, are in need of review.